Successful Management of Spontaneous Unilateral Twin Ectopic Pregnancy With Two-Step Dose of Methotrexate - Lauren A. Forbes; Navya Nuthivana; Renee Morales (Case Reports in Obstetrics and Gynecology)
The incidence of unilateral tubal twin pregnancy is 1/20,000–1/250,000 with about 100 reported cases. Four of the six cases that were medically managed were successful. A 24-year-old female presented to the emergency department (ED) with vaginal bleeding and abdominal cramping. She was hemodynamically stable without signs of an acute abdomen. Laboratory evaluation revealed she was pregnant with a serum beta-human chorionic gonadotropin (b-hCG) of 798 mIU/mL. Transvaginal ultrasound (TVUS) revealed a single left tubal pregnancy with a yolk sac. The patient elected medical management with body surface area (BSA)–based intramuscular (IM) methotrexate (MTX). On Day 4, the patient returned to the ED; her b-hCG was 727 mIU/mL. TVUS revealed twin left tubal pregnancies with yolk sacs and fetal poles without cardiac activity. The patient elected to continue medical management with a second dose of BSA-based IM MTX. On Day 6, the patient returned to the ED with abdominal and rectal pain. She was hemodynamically stable without signs of an acute abdomen. Her b-hCG was 533 mIU/mL. TVUS showed persistent twin left tubal pregnancies—one at 5 weeks gestational age and the other at 6 weeks gestational age—without evidence of rupture. The patient continued serial b-hCGs. Thirty-one days after the first dose of MTX, her b-hCG was < 1 mIU/mL. TVUS showed resolution of tubal pregnancies. The patient consented to the publication of this case report. This case documents the successful treatment of spontaneous, unilateral tubal twin pregnancies with two-step dosing of IM MTX.